Social Construction and Social Status Conflict in Qais Figure in Layla Majnun Novel by Nizami (Sociology of Literature Perspective) - Suci Veramitha Apriani; Mohammad Rosyid Ridho; Yadi Mardiansyah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Social construction and social status conflict are important issues in literary sociology studies, including in Nizami's Layla Majnun. The character of Qais in this novel represents the complex dynamics between social norms, societal expectations, and personal identity. This study aims to describe how social construction shapes Qais' role and position in society, as well as how social status conflict affects his life journey and choices. The method used is descriptive qualitative with a sociology of literature approach. The results show that Qais experiences strong social pressure due to class differences and cultural norms that hinder his love for Layla. Qais' social status as a poet who is considered crazy by society symbolizes resistance to rigid social constructions. The character of Qais represents an individual trapped in a social system that does not give him space, but still shows sincerity and firmness in defending his love and beliefs. The findings provide a deeper understanding of the impact of social construction on individual freedom and the relevance of social status conflict in modern life.